Efficacy of transcranial Direct Current Stimulation (tDCS) combined with intensive speech therapy for language production in monozygotic twins with corpus callosum dysgenesis (CCD): A sham-controlled single subject study. Issue 2 (4th March 2022) - Mousavi, Najva; Nitsche, Michael A.; Jahan, Ali; Nazari, Mohammad Ali; Hassanpour, Hassan
ABSTRACT: The purpose of this single subject study was to investigate whether transcranial direct current stimulation (tDCS) applied to both hemispheres combined with speech therapy can improve language learning in a pair of 5-year-old twins with corpus callosum dysgenesis (CCD). The treatment protocol included anodal tDCS with simultaneous speech therapy in one of the participants (T.D.), and sham-tDCS with the same montage, and stimulation regime concomitant with speech therapy for the other twin (A.D.). Our findings show that T.D. improved in language production when treated with speech therapy in combination with tDCS. A.D. showed evidence for a relatively minor behavioral benefit from speech therapy.